The Influence of Career Development, Work Environment and Work Discipline on Employess Performance of PT. Sintertech - Effendy, Ervina Elia; Gopar, Ida Abdul (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to find out the influence of Career Development (X1), Work Environment (X2), and Work Discipline (X3) on Employee Performance (Y) at PT. Sintertech is a company engaged in the field of technology synthesis. This research uses quantitative methods, the population taken comes from employees of PT. Sintertech conducted a study using a sample size of 90 participants and collected data through questionnaires. This research method uses non-probability sampling techniques with data analysis methods in the form of Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, and Hypothesis Testing using partial. The results of the T (Partial) test on career development have a positive and significant effect with a calculated t value > t table t table (8.553> 1.987) and significant 0.000 <0.05, work environment variables have a positive and significant effect with the value of t count> t table (2.096> 1.987) and significance 0.039 <0.05, work discipline variables have a positive and significant effect with the value of t count> t table (38.025> 1.987) and significant 0.000 <0.05. Simultaneously, Career Development, Work Environment, and Work Discipline have a significant effect on employee performance with the results of the F test significant value of 0.000 <0.05.